Crossing Borders in East Asian Higher Education
XVI, 388 p. 3 illus.
Keywords: This book examines issues that have emerged as higher education systems and individual institutions across East Asia confront and adapt to the changing economic, social, and educational environments in which they now operate. The book' s focus is on how higher education systems learn from each other and on the ways in which they collaborate to address new challenges. The sub-theme that runs through this volume concerns the changing nature of cross-border sharing. In particular, the provision of technical assistance by more industrialized countries to lower and middle income countries has given way to collaborations that place the latter' s participating institutions on a more equal footing. At the same time, there is a greater number of partnerships that link higher education systems in the East Asian region to one another. Even as boundaries become more porous and permeable, there is growing acceptance of the view that cross border collaboration, if done well, can offer mutually beneficial advantages on multiple levels. There is a new recognition that the intensified international sharing of ideas, strategies of learning, and students is not only of enormous value to systems and institutions but essential to their long term survival. To this end, the chapters in this volume examine various motivations, goals, mechanisms, outcomes and challenges associated with cross-border collaboration in higher education. Crossing Borders in East Asian Higher Education was awarded 1st place in the Annual Comparative and International Education Society's Higher Education SIG in the category Best in Book for 2009-2010 academic year. .